2013
DOI: 10.1155/2013/898034
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and Its Neurotoxic Effects

Abstract: Cadmium (Cd) is a heavy metal that has received considerable concern environmentally and occupationally. Cd has a long biological half-life mainly due to its low rate of excretion from the body. Thus, prolonged exposure to Cd will cause toxic effect due to its accumulation over time in a variety of tissues, including kidneys, liver, central nervous system (CNS), and peripheral neuronal systems. Cd can be uptaken from the nasal mucosa or olfactory pathways into the peripheral and central neurons; for the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
269
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(301 citation statements)
references
References 103 publications
(109 reference statements)
4
269
1
5
Order By: Relevance
“…Cadmium affects the proliferation and differentiation of cells. Cadmium damages DNA, membranes, and proteins, and inhibits DNA repair in different ways [4,[12][13][14] . In this study, we demonstrated that Cd 2+ also decreases the cell viability of middle ear epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium affects the proliferation and differentiation of cells. Cadmium damages DNA, membranes, and proteins, and inhibits DNA repair in different ways [4,[12][13][14] . In this study, we demonstrated that Cd 2+ also decreases the cell viability of middle ear epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium (Cd 2+ ) is a heavy metal that is considered to be one of the most common environmental and occupational hazards [4] . Groups at high risk of cadmium exposure include people who live in contaminated areas, people who have a higher intake of cadmium through diet, or those who smoke cigarette as well as women [5] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it may alter accumulation of amyloid. For example, Cadmium increases amyloid precursor protein synthesis [18] and alters amyloid beta peptide membrane channel resulting in large aggregates of precipitationprone amyloid in cells [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Od blokatora Ca 2+ kanala prisutnih u životnoj sredini Cd 2+ zaslužuje posebnu pažnju. Epidemiološke studije su pokazale da je veliki deo populacije stalno izložen toksičnom delovanju Cd 2+ u radnoj i životnoj sredini, preko vode, hrane i naročito cigareta, kao i da Cd 2+ dovodi do neuroloških poremećaja [23]. U kontekstu naših istraživanja posebno je interesantno da ponavljana primena Cd 2+ kod pacova dovodi do promena u spontanoj aktivnosti korteksa sa povećanjem frekvencije talasa na elektrokortikogramu [24] kao i do pojave epileptiformne aktvnosti na EEG-u [25].…”
Section: Diskusijaunclassified